Hypertensive retinopathy in the end-stage renal failure – study case - Kal, Magdalena; Mackiewicz, Jerzy (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
The case of 26-year-old woman with a transient deterioration of binocular vision secondary to chronic renal failure due to glomerulonephritis is presented. The patient reported the onset of the disease at the age of 2. As her kidney disease was poorly controlled, she developed renal hypertension followed by bilateral hypertensive retinopathy. The patient was hospitalized in the Department of Nephrology, where she received dialyses and her blood pressure was normalised. The follow up in the Ophthalmology Clinic was continued for 9 months. The treatment of her primary disease resulted in a significant resolution of retinopathy and improved her visual acuity.